Factors Influencing Students’ Cheating Behaviours: An Empirical Evidence from China - Wang, Lei; Tan, Xiong Fei; Wang, Zi Xu; Wong, Philip Pong Weng (International Journal of Education, Science, Technology, and Engineering (IJESTE), 2023)
There is an ample evidence to show how students’ cheating behaviours formed in Western countries, comparatively, few studies focused on Chinese students. The purpose of this study is to measure the influence of attitude, subjective norm (SN), perceived behavioural control (PBC), and additional variable which is moral obligation on intention among Chinese students who were studying in China and the U.K. A total of 540 useable questionnaires were collected based on web-based method for further hypotheses testing. The results show that attitude, SN, PBC and moral obligation positively influence intention to cheat respectively. The SN displays significant positive influence on attitude and moral obligation. In addition, statistically significant differences in SN, PBC and intention were obtained between gender, majors and educational level and studying places which show that males had more intention than females on cheating. Major of management students had more PBC than engineering and economics students, fresh and sophomore had more PBC than junior students, and students who were studying in U.K are more influenced by SN compared to who were studying in China. This study enriches the existing knowledge on how Chinese students’ attitude, SN, PBC and moral obligation on cheating intention based on divergent demographic characteristics.